Whither energy cooperation in Latin America? - Flores-Quiroga, A (Oxford Institute for Energy Studies, 2015)
Two features of Latin America’s energy sector – its position as a net energy exporter and the recent build-up of LNG importing facilities on both its Atlantic and Pacific coasts – illustrate both the potential for energy cooperation in the region and the associated pitfalls. The first, which is an expression of energy abundance, hints at the promise of integration; but the second suggests this might be wishful thinking, at least for the time being. The future of Latin American energy cooperation will depend largely on which of these two conflicting tendencies prevails.